Careglove Global Sdn Bhd / Muhammad Afifi Kamarudzaman - Kamarudzaman, Muhammad Afifi (Faculty Of Chemical Engineering, 2021)
Careglove Global Sdn Bhd has given me a lot of opportunities to learn on how to work in the field. Throughout my internship program for 17 weeks, I have already adapted to the working environment. I have learnt a lot from my supervisor and other colleagues on run the daily work in the stripping and dipping area. I am thankful for all the knowledges that I have gained throughout my internship program. As student, is important for us to learn and have the real working environment and experience so that it would be easy for us to work in the field in the future. Working in the al field is not just about applying the knowledge that we learnt in university, but it is also out learning on how to adapt with the real situation. In my opinion, we as a person must 3ve the ability to learn to be a fast worker and to adapt with the task and job assigned for conclude, my internship has been excellent for various reasons and the best part is I had he opportunity on working a field related to my course, Diploma in Chemical Engineering. It was a wonderful journey I had with the job that I have been assigned with and it was a great memory for me to get to know everyone in the company that has helped me in numerous ways.